Invasion of Aedes albopictus (Diptera: Culicidae) into central Africa: what consequences for emerging diseases? - (:unkn) unknown (My University, 2015)
Aedes albopictus, a mosquito native to Asia, has invaded all five continents during the past three decades. It was reported in central Africa in the 2000s, first in Cameroon, and, since then, has colonised almost all countries of the region. The species, originally considered a secondary vector of dengue viruses, has been showed to play a major role in transmission of chikungunya virus in numerous countries, including in the central African region. We review the current spread of Ae. albopictus in central Africa, its larval ecology and its impact on indigenous species such as Ae. aegypti. We explore the potential of Ae. albopictus to affect the epidemiology of emerging or re-emerging arboviruses and discuss the conventional means for its control, while emphasizing the importance of data on its susceptibility to insecticides to cope with potential outbreaks.
Keywords: African Research